Electoral systems and political participation in local and legislative elections of Iraq - HAMZAH , A.G. (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT Dawn of March 19, 2003, the coalition forces ended the dictatorial regime that had lingered for more than 30 years, liberating Iraqis and help them make the shift to a democratic system. Nevertheless, religious groups and parties supported by neighboring countries managed to seize power in a very short period. They succeeded in manipulating the electoral system and deform the applied Saint – Lego system in a way that serves their political agenda. RESUMEN Al amanecer del 19 de marzo de 2003, las fuerzas de la coalición acabaron con el régimen dictatorial que había durado más de 30 años, liberando a los iraquíes y ayudándoles a dar el paso al sistema democrático. Sin embargo, grupos y partidos religiosos apoyados por países vecinos lograron tomar el poder en un período muy corto. Lograron manipular el sistema electoral y deformar el sistema Saint-Lego aplicado de una manera que sirva a su agenda política.